Nanomaterial-mediated low-temperature photothermal therapy via heat shock protein inhibition - Xin, Yu; Sun, Zhuokai; Liu, Jie; Li, Wei; Wang, Meirong; Chu, Yongli; Sun, Zhihong; Deng, Guanjun (Frontiers in Bioengineering and Biotechnology, 2022)
With the continuous development of nanobiotechnology in recent years, combining photothermal materials with nanotechnology for tumor photothermal therapy (PTT) has drawn many attentions nanomedicine research. Although nanomaterial-mediated PTT is more specific and targeted than traditional treatment modalities, hyperthermia can also damage normal cells. Therefore, researchers have proposed the concept of low-temperature PTT, in which the expression of heat shock proteins (HSPs) is inhibited. In this article, the research strategies proposed in recent years based on the inhibition of HSPs expression to achieve low-temperature PTT was reviewed. Folowing this, the synthesis, properties, and applications of these nanomaterials were introduced. In addition, we also summarized the problems of nanomaterial-mediated low-temperature PTT at this stage and provided an outlook on future research directions.